The histories of Raphael Samuel : a portrait of a people's historian - Scott-Brown, Sophie (2017)
In the first integrated biographical study of his work, this book situates British historian Raphael Samuel (1934–1996) in relation to his distinctive form of activist politics as they developed from youthful Cold War communism to the first British New Left, 1960s radicalism to the 1980s history wars. As the catalyst behind the History Workshop movement, Samuel championed the democratisation of history-making and practised an eclectic form of people's history in his own work. His unique approach was controversial, drawing impassioned responses from across the ideological spectrum, the most sustained critique often coming from his left-wing contemporaries. It is argued here that this compelling figure has been unjustly neglected and that he continues to offer important insights into the politics of history-making in a post-Marxist world.